2019
DOI: 10.1093/infdis/jiz145
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of False Elite Controllers: HIV Antibody-Positive RNA-Negative Blood Donors Found To Be on Antiretroviral Therapy

Abstract: Background An increase in potential HIV elite controllers (EC) and anecdotal reports of antiretroviral therapy (ART) use among South African blood donors led us to verify EC status. Methods Stored plasma samples from potential EC were tested for ART drugs. Demographic and temporal associations were examined using multivariable logistic regression. Results Of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
47
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(53 citation statements)
references
References 14 publications
2
47
2
Order By: Relevance
“…Concerns have been raised over donors using HIV preexposure prophylaxis or antiretroviral treatments not reporting drug intake, risk exposure, or infectious status. Recent studies have reported the presence of antiretroviral drugs in donated blood . Viral loads suppressed below the screening assay LOD as a result of these treatments may still be high enough in contaminated donations to lead to TTI .…”
Section: Discussionmentioning
confidence: 99%
“…Concerns have been raised over donors using HIV preexposure prophylaxis or antiretroviral treatments not reporting drug intake, risk exposure, or infectious status. Recent studies have reported the presence of antiretroviral drugs in donated blood . Viral loads suppressed below the screening assay LOD as a result of these treatments may still be high enough in contaminated donations to lead to TTI .…”
Section: Discussionmentioning
confidence: 99%
“…The LAg avidity assay is known to falsely classify as 'recent' approximately 60% of donors on anti‐retroviral therapy (ART) and 13% of Elite controllers as recent infections [5, 7] due to a muted immune response especially if treatment is started early after acquisition [23, 24]. To mitigate this we excluded all donations that tested ID‐NAT negative, anti‐HIV positive – which is the test result pattern most commonly seen among HIV‐positive donors taking surreptitious ART [25]. However, it is possible that some of our ID‐NAT positive donors could be on ART with incomplete viral suppression and hence falsely classified as recent infections [25].…”
Section: Discussionmentioning
confidence: 99%
“…The motto “undetectable equals untransmittable,” which is relevant to the risk of transmission through sexual contact, does not for the moment apply to the situation where someone is transfused a large volume of blood. Also, it has recently been shown that some HIV‐positive donors were taking antiretroviral drugs at the time of their donation, suggesting that they were under the impression of not being at risk of transmitting their infection through transfusion . Another study done among HIV‐negative male blood donors, yet to be published, also showed that a small but nontrivial number of them were taking antiretroviral drugs.…”
mentioning
confidence: 99%
“…Also, it has recently been shown that some HIV-positive donors were taking antiretroviral drugs at the time of their donation, suggesting that they were under the impression of not being at risk of transmitting their infection through transfusion. 11,12 Another study done among HIV-negative male blood donors, yet to be published, also showed that a small but nontrivial number of them were taking antiretroviral drugs. These could just represent another instance of noncompliance by some donors who consider themselves at no risk of transmitting the infection, regardless of the eligibility criteria being applied.…”
mentioning
confidence: 99%